2006
DOI: 10.1111/j.1365-263x.2006.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms from ectodermal organs in young Swedish individuals with oligodontia

Abstract: An early identification of individuals with oligodontia can be made in a majority of cases by checking that all permanent incisors have erupted at the age of 8 years. The validity in asking individuals about normal and abnormal function of ectodermal organs was found to be low. This indicates that there is a strong need to establish routine clinical criteria for dysplasia of ectodermal organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 12 publications
(24 reference statements)
2
29
1
3
Order By: Relevance
“…As it was reported previously and as in our study, the most common missing tooth was the maxillary lateral incisor, followed by bicuspids (Szepesi, 2006;Altug-Atac, 2007;Gábris, 2006). In contrast, other studies reported that bicuspids were the most common missing teeth (Bergendal et al, 2006 Onyeaso, 2006), and the data regarding fused teeth in our study were higher since they were 4.3% of the whole sample and the third more frequent diagnosed entity. It is important to have a close follow-up with these patients in order to prevent future problems during exfoliation of the fused teeth and eruption of the succedaneous one (Ledesma-Montes et al, 2012a).…”
Section: Discussioncontrasting
confidence: 54%
“…As it was reported previously and as in our study, the most common missing tooth was the maxillary lateral incisor, followed by bicuspids (Szepesi, 2006;Altug-Atac, 2007;Gábris, 2006). In contrast, other studies reported that bicuspids were the most common missing teeth (Bergendal et al, 2006 Onyeaso, 2006), and the data regarding fused teeth in our study were higher since they were 4.3% of the whole sample and the third more frequent diagnosed entity. It is important to have a close follow-up with these patients in order to prevent future problems during exfoliation of the fused teeth and eruption of the succedaneous one (Ledesma-Montes et al, 2012a).…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, oligodontia represents a more severe clinical expression of disturbed tooth development than hypodontia. Individuals with oligodontia constitute approximately 1% of all individuals with hypodontia, and both conditions may be found in the same family, indicating variable expression of shared genetic factors [Polder et al, 2004;Bergendal et al, 2006]. In this study we used a population-based approach to clarify the prevalence of mutations in the AXIN2, MSX1, PAX9, EDA, EDAR, and EDARADD genes in non-syndromic oligodontia.…”
mentioning
confidence: 99%
“…In both studies the subjects were recruited from specialist centers. Epidemiological studies from a cohort of Swedish children estimated the prevalence of oligodontia with or without additional ectodermal signs and symptoms to 0.09% [Bergendal et al, 2006]. Within this cohort, structured interviews of 114 individuals with non-syndromic oligodontia showed 12 individuals (10.5%) with self-reported abnormal hair, nails, or sweating.…”
mentioning
confidence: 99%
“…EDs comprise a large heterogeneous group of genetic disorders with developmental abnormalities in two or more of the following ectodermal structures: teeth, skin, sweat glands, nails and hair. The salivary glands are ectodermal in origin, and reduced salivary secretion has been demonstrated in both ED and isolated oligodontia [4,5]. In these conditions, it is also common for present teeth to be peg-shaped.…”
Section: Introductionmentioning
confidence: 99%